2007
DOI: 10.1159/000109471
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Atypical PML-RARA Breakpoint in a Patient with Acute Promyelocytic Leukemia

Abstract: Acute promyelocytic leukemia (APL) of the M3 subtype is characterized by translocation t(15;17) that generates the PML-RARA fusion gene. Depending on the breakpoint position in the PML gene, 3 main fusion transcripts usually result. These breakpoints are bcr1 and bcr3 in introns 6 and 3, respectively, and bcr2 in exon 6. This report describes a rare atypical bcr2 breakpoint in a patient with morphological, cytogenetic and molecular features of APL. The presence of t(15;17) was first revealed by fluorescent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These are characterized by cDNA deletions of either the distal region of PML exon 6 (from 8 to 146 nucleotides), or the entire exon 6, as a result of a mis-splicing event or a genomic break within PML exon 6 (rarely in PML exon 5). Likewise, atypical bcr2 are frequently associated with insertions of three to 127 extra nucleotides (1 to 42 extra amino acids) of genomic DNA from RARA intron 2 [63,[68][69][70][71][72][73][74]. In most of the cases, V-forms are "private", being observed in single APL patients.…”
Section: Pml-rara Atypical Isoformsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are characterized by cDNA deletions of either the distal region of PML exon 6 (from 8 to 146 nucleotides), or the entire exon 6, as a result of a mis-splicing event or a genomic break within PML exon 6 (rarely in PML exon 5). Likewise, atypical bcr2 are frequently associated with insertions of three to 127 extra nucleotides (1 to 42 extra amino acids) of genomic DNA from RARA intron 2 [63,[68][69][70][71][72][73][74]. In most of the cases, V-forms are "private", being observed in single APL patients.…”
Section: Pml-rara Atypical Isoformsmentioning
confidence: 99%
“…In most of the cases, V-forms are "private", being observed in single APL patients. However, a few cases share the activation of a novel donor splice site in PML exon 6 [72,73], or express a minor PML-RARA transcript with exon 5 skipped [72,74]. Reported isoforms have been compared with the reference sequences of PML and RARA (GenBank accession numbers: NM_033238.2; NM_000964.3).…”
Section: Pml-rara Atypical Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical and biological impact of these atypical isoforms remains unclear. A few reports demonstrated that PML break points downstream intron 6 are potentially associated with poor prognosis and an aggressive disease course, whereas other studies described cases with atypical PML/RARA with clinical outcome similar to that of patients with typical fusion transcripts …”
Section: Introductionmentioning
confidence: 99%
“…A few reports demonstrated that PML break points downstream intron 6 are potentially associated with poor prognosis and an aggressive disease course, [8][9][10][11] whereas other studies described cases with atypical PML/RARA with clinical outcome similar to that of patients with typical fusion transcripts. 9,[12][13][14][15][16] In this study, we report the characterization of three cases of APL with novel atypical PML/RARA transcripts, which were not clearly detectable using standard molecular procedure.…”
mentioning
confidence: 99%